A phase III randomized, open-label, non-inferiority clinical trial comparing liquid and lyophilized formulations of oral live attenuated human rotavirus vaccine (HRV) in Indian infants. Issue 11 (2nd November 2021) - Cohet, Catherine; Cheuvart, Brigitte; Moerman, Leentje; Bi, Dan; Caplanusi, Adrian; Kariyappa, Mallesh; Lalwani, Sanjay; Mitra, Monjori; Sapru, Amita; Saha, Shruti; Varughese, P.V.; Kompithra, Rajeev Zachariah; et al.
ABSTRACT: The human rotavirus vaccine (HRV; Rotarix, GSK) is available as liquid (Liq) and lyophilized (Lyo) formulations, but only Lyo HRV is licensed in India. In this phase III, randomized, open-label trial (NCT02141204), healthy Indian infants aged 6–10 weeks received 2 doses (1 month apart) of either Liq HRV or Lyo HRV. Non-inferiority of Liq HRV compared to Lyo HRV was assessed in terms of geometric mean concentrations (GMCs) of anti-RV immunoglobulin A (IgA), 1-month post-second dose (primary objective). Reactogenicity/safety were also evaluated. Seroconversion was defined as anti-RV IgA antibody concentration ≥20 units [U]/mL in initially seronegative infants (anti-RV IgA antibody concentration <20 U/mL) or ≥2-fold increase compared with pre-vaccination concentration in initially seropositive infants. Of the 451 enrolled infants, 381 (189 in Liq HRV and 192 in Lyo HRV group) were included in the per-protocol set. The GMC ratio (Liq HRV/Lyo HRV) was 0.93 (95% confidence interval [CI]: 0.65–1.34), with the lower limit of the 95% CI reaching ≥0.5, the pre-specified statistical margin for non-inferiority. In the Liq HRV and Lyo HRV groups, 42.9% and 44.3% (baseline) and 71.4% and 73.4% (1-month post-second dose) of infants had anti-RV IgA antibody concentration ≥20 U/mL, and overall seroconversion rates were 54.5% and 50.0%. Incidences of solicited and unsolicited adverse events were similar between groups and no vaccine-related serious adverse events were reported. Liq HRV was non-inferior to Lyo HRV in terms of antibody GMCs and showed similar reactogenicity/safety profiles, supporting the use of Liq HRV in Indian infants. PLAIN LANGUAGE SUMMARY: What is the context? Rotavirus is the most common cause of acute gastronenteritis and contributes to the high number of hospitalizations and deaths in young children worldwide. Vaccination against rotavirus has led to a significant decrease in rotavirus-related infections. The human rotavirus vaccine Rotarix (GSK) is currently used as a liquid or lyophilized formulation. In clinical trials conducted in European and North American infants, the liquid vaccine showed ability to induce immune response and safety comparable to the lyophilized formulation. Only the lyophilized vaccine is currently marketed in india. What is new? We compared the 2-dose liquid and lyophilized human rotavirus vaccines in indian infants in a phase III clinical trial: The ability to induce immune response for thw liquid formulation was not inferior to that observed for the lyophilized vaccine. The safety profiles of the 2 formulations were comparable. Why is this important? This study shows that the liquid human rotavirus vaccine can be administrated to infants from india.